Multi-UAV Collaborative Covert Communications: An ISAC-based Approach - Weijie YUAN; Jun WU; Yuye SHI (Leida xuebao)
Covert Unmanned Aerial Vehicle (UAV) communication has garnered considerable attention for realizing a sustainable Low-Altitude Economy (LAE). Based on the Integrated Sensing And Communication (ISAC) framework, this paper studies the system strategies and resource allocation for a cooperative multi-UAV covert communication network, where multiple UAVs are employed to simultaneously conduct cooperative sensing and covert downlink transmissions to multiple Ground Users (GUs) in the presence of a mobile warden (Willie). To improve communication covertness, UAVs adaptively switch between Jamming Unmanned Aerial Vehicle (JUAV) mode and Information Unmanned Aerial Vehicle (IUAV) mode. To cope with the mobility of Willie, an Unscented Kalman Filtering (UKF)-based method is employed to track and predict Willie's location using delay and Doppler measurements extracted from ISAC echoes. By jointly optimizing the JUAV selection strategy, IUAV-GU scheduling, and communication/jamming power allocation, a real-time fairness transmission maximization problem is formulated. The Alternating Optimization (AO) approach is adopted to decompose the original problem into a series of sub-problems, resulting in an efficient sub-optimal solution. Simulation results demonstrate that the proposed scheme can accurately track Willie and effectively ensure covert downlink transmission.